Accelerating semogenesis: an ecosocial approach to photography. (November 2021) - Johannessen, Christian Mosbæk; Boeriis, Morten
Michael Halliday and Christian Matthiessen's term 'semogenesis' refers to how meaning potentials are created through processes on many co-occurring time frames, most prominently those referred to as 'phylogenesis', 'ontogenesis' and 'logogenesis'. The concept was originally infused with linguistic concern in an attempt to link a Systemic Functional Linguistics (SFL) account of the lexico-grammatical and semantic strata with lived experience. In this article, the authors rethink the concept in order to (1) broaden its scope to the concerns of multimodal studies, and (2) accommodate how digital technology impacts on our communication practices. They do so by discussing semogenesis from a vantage point of 'ecosocial semiotics', a perspective that asks us to blend both sociological, technological, material and biological understandings of human activity. Taking digital photography as an example, the authors argue that digital media afford an acceleration of processes of multimodal semogenesis on all semogenetic time frames. Picking up the notion of 'microgenesis', a fourth, faster-than-logogenesis time frame that serves as a placeholder for any process enabling logogenesis, they suggest that this acceleration is driven by the global-scale introduction of digital technology. Through a discussion of select examples from the history of photography, specifically contrasting nascent photographic practice with contemporary photography, they propose that the development from camera to digital camera and the subsequent consolidation in recent decades of digital cameras into smartphones has had a profound impact, not only on practices of photography, but also on the processes of meaning making with photographic material.